Balancing harms and benefits of service mammography screening programs: a cohort study - Puliti, Donella (BioMed Central, 2012)
INTRODUCTION: The use of screening mammography is still under debate within the medical community. The aim of this study is to define a balance sheet of benefits (breast cancer mortality reduction) and harms (overdiagnosis) for mammography screening programs. METHODS: We compared breast cancer incidence and mortality in two cohorts of women, defined as 'attenders' or 'non-attenders' on the basis of the individual attitudes towards screening, who were invited to the first round of the Florentine screening program. The effects of screening exposure on breast cancer incidence and mortality were evaluated by fitting Poisson regression models adjusted for age at entry, marital status and deprivation index. We performed a sensitivity analysis excluding 34 women not responding to the invitation with a breast cancer diagnosis in the following six months. RESULTS: In total, we included 51,096 women aged 50 to 69 years invited at the first screening round (1991 to 1993) and followed-up for breast cancer incidence and mortality until 31 December 2007 and 31 December 2008, respectively The estimate of mortality reduction varies from 45% among 50 to 59 year-old women up to 51% among 60 to 69 year-old women. The estimate of overdiagnosis, according to the cumulative-incidence method, is an additional 10% of all breast cancer cases among 60 to 69 year-old women screened. CONCLUSIONS: Comparing the breast cancer mortality and breast cancer incidence between attenders and non-attenders, we have determined that the overall cost to save one life corresponds to no more than one over-diagnosed tumor (from 0.6 to 1 depending on the selection criteria of the cohort), even if a residual self-selection bias cannot be excluded.